Opportunities and Limits of Sacramentality: what do we Learn from the Debate on Fiducia Supplicans - Grillo, Andrea (Concilium, 2025)
The Note Fiducia supplicans brings to light two important misunderstandings that characterise the entire modern Catholic tradition: the claim to identify a sacrament in every marital contract between baptised people, and to extend ecclesial competence to cover the entire scope of sexual and relational life. The consequence of this movement, which began with Tametsi (1563), is the progressive marginalisation of blessing, in favour of consent, as the centre of the sacrament. A recovery of the value of the blessing, however, does not allow us to identify a "pastoral blessing" that is not liturgical and ritual. This is an impossible claim: the blessing as such is liturgical and ritual. Projecting Tametsi's need for control onto the blessing constitutes a contradiction in terms, which effectively makes the opening of Fiducia supplicans inconsistent and only fuels clandestine pastoral care.